Deformation and Gravity Change: Indicators of Isostasy, Tectonics, Volcanism, and Climate Change - Wolf, Detlef; Fernández, José.; SpringerLink (Online service) (Basel : Birkhäuser Basel : Imprint: Birkhäuser, 2007)
During the last decades, measurements of various geodynamic processes have gained ever increasing importance. Temporal variations of the deformation and gravity fields monitored by geodetic measuring techniques reflect isostatic, tectonic or volcanic processes in the earth’s interior. Recordings of hydrologic or oceanographic phenomena allow conclusions on surface processes. This volume reflects the major developments during recent years in these areas of research. Most of the papers in this book were presented at the workshop on "Deformation and Gravity Change: Indicators of Isostasy, Tectonics, Volcanism and Climate Change", which took place at the Casa de los Volcanes on Lanzarote, Spain, during March 1-4, 2005. It was jointly organized and supported by the International Association of Geodesy (IAG), the Spanish Ministry of Education and Science, the Spanish Council for Scientific Research and the Cabildo Insular de Lanzarote. The workshop also served as the first meeting of the members of the IAG Working Group ICCT2 on "Dynamic Theories of Deformation and Gravity Fields".
Deformation and Gravity Change: Indicators of Isostasy, Tectonics, Volcanism and Climate Change. Introduction -- An Overview of the Small BAseline Subset Algorithm: A DInSAR Technique for Surface Deformation Analysis -- Propagator-matrix Technique for the Viscoelastic Response of a Multi-layered Sphere to Surface Toroidal Traction -- Using Fuzzy Logic for the Analysis of Sea-level Indicators with Respect to Glacial-isostatic Adjustment: An Application to the Richmond-Gulf Region, Hudson Bay -- Shear-wave Velocity Structure around Teide Volcano: Results Using Microtremors with the SPAC Method and Implications for Interpretation of Geodetic Results -- Steric Sea-level Variations Inferred from Combined Topex/Poseidon Altimetry and GRACE Gravimetry -- Interpretation of 1992–1994 Gravity Changes around Mayon Volcano, Philippines, Using Point Sources -- Glacial-isostatic Adjustment and the Viscosity Structure Underlying the Vatnajökull Ice Cap, Iceland -- Review of Microgravity Observations at Mt. Etna: A Powerful Tool to Monitor and Study Active Volcanoes -- An Estimate of Global Mean Sea-level Rise Inferred from Tide-gauge Measurements Using Glacial-isostatic Models Consistent with the Relative Sea-level Record -- Modeling of Stress Changes at Mayon Volcano, Philippines -- A Hybrid Model for the Summit Region of Merapi Volcano, Java, Indonesia, Derived from Gravity Changes and Deformation Measured between 2000 and 2002 -- Vertical Crustal Motion along the Mediterranean and Black Sea Coast Derived from Ocean Altimetry and Tide Gauge Data -- Some Insights into Topographic, Elastic and Self-gravitation Interaction in Modelling Ground Deformation and Gravity Changes in Active Volcanic Areas.
Keywords: Geophysics; Atmospheric sciences; Economic geology; Geotechnical engineering; Geophysics and Environmental Physics; Atmospheric Sciences; Economic Geology; Geotechnical Engineering & Applied Earth Sciences; Geophysics/Geodesy.